Tantangan Penegakan Hukum Terhadap Tindak Pidana Korupsi oleh Perusahaan Multinasional - Dwight Nusawakan; Abdul Malik Mufty; Muh Anugrah Kurniawan Amir (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
The phenomenon of transnational corruption involving foreign corporate entities poses significant challenges to the national criminal justice system, particularly in asserting jurisdiction and enforcing sanctions. Although legal frameworks such as the 2023 Indonesian Penal Code, the Law on the Eradication of Corruption, the Law on the Corruption Eradication Commission, and the Law on Mutual Legal Assistance in Criminal Matters are already in place, the prosecution of multinational corporations remains hindered by structural barriers and implementation gaps. This research aims to analyze the legal challenges faced by Indonesia in prosecuting foreign corporations engaged in corruption and to formulate appropriate legal strategies to address these obstacles. The research method employed is normative legal research using statute and conceptual approaches, drawing on primary legal materials (statutory regulations), as well as secondary and tertiary legal sources. The findings reveal the urgent need for enforcement reforms through jurisdictional innovation, strengthened international cooperation, and the adoption of progressive legal theory and developmental law approaches to ensure legal certainty and effectiveness in addressing global corporate crime.